2021
DOI: 10.1136/tobaccocontrol-2020-056080
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported exposure of Indonesian adolescents to online and offline tobacco advertising, promotion and sponsorship (TAPS)

Abstract: ObjectivesTo quantify tobacco advertising, promotion and sponsorship (TAPS), self-reported exposure from online and offline platforms among adolescents in Indonesia.MethodsA cross-sectional school-based survey was conducted in 2017. In total, 2820 students aged 13–18 years were recruited from 22 schools in seven cities. Respondents reported TAPS exposure on online (online news, YouTube, Facebook, Twitter and Instagram), and offline platforms (broadcast media, tobacco industry sponsored events and outdoor adver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 22 publications
3
24
0
4
Order By: Relevance
“…Penayangan iklan rokok dapat ditemui dalam berbagai bentuk, salah satunya secara online dan offline. Dalam penelitian (Septiono et al, 2021), 2820 siswa usia 13 -18 tahun melaporkan paparan penyangan iklan, promosi, dan sponsor rokok dapat ditemukan pada media online (berita online, YouTube, Facebook, Twitter, dan Instagram) dan offline (media penyiaran, acara dengan sponsor rokok, dan media iklan luar ruang).…”
Section: Pembahasanunclassified
See 1 more Smart Citation
“…Penayangan iklan rokok dapat ditemui dalam berbagai bentuk, salah satunya secara online dan offline. Dalam penelitian (Septiono et al, 2021), 2820 siswa usia 13 -18 tahun melaporkan paparan penyangan iklan, promosi, dan sponsor rokok dapat ditemukan pada media online (berita online, YouTube, Facebook, Twitter, dan Instagram) dan offline (media penyiaran, acara dengan sponsor rokok, dan media iklan luar ruang).…”
Section: Pembahasanunclassified
“…Jurnal Kesehatan Masyarakat ISSN (Online) : 2797-6424 (Facebook dan Instagram) sebagai sarana promosi. Selain itu, pada iklan tidak dicantumkan batasan usia, sehingga terdapat indikasi remaja untuk melihat iklan ini (Septiono et al, 2021). Iklan rokok melalui media online berpengaruh pada pengetahuan, sikap, dan perilaku remaja (Catherine et al, 2012).…”
Section: Health Publicaunclassified
“…A study conducted in 2017 on self-reported TAPS exposure from online and offline platforms among 2820 school-aged adolescents from 22 schools in 7 cities of Indonesia found that exposure to TAPS on online platforms was high on Instagram (29.6%), while in terms of offline avenues, TAPS exposure was high on television (74.0%), through billboards (54.4%), and at live music events (46.2%). The students also reported seeing outdoor advertising mainly on the streets and at minimarkets [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…TAPS ban is one of the MPOWER strategy and is included in the 'Best Buys' for effective tobacco control (WHO, 2020). However, many countries, especially low-income and middle-income countries, primarily implement only partial TAPS bans, allowing the tobacco industry to directly or indirectly advertise and promote its products via multiple media (Septiono et al, 2021). Moreover, increasingly, a large proportion of tobacco advertising and promotion is being accomplished through emerging media such as websites and social media or at music and sports events which are increasingly becoming popular (Astuti and Freeman, 2018).…”
mentioning
confidence: 99%
“…Also, online and social media are borderless and can reach out to populations well beyond a country's administrative and regulatory borders. Thus, populations worldwide, including adolescents and children, are vulnerable to exposure to TAPS from countries with insufficient and weak legislation (Septiono et al, 2021). This has further aggravated in light of emerging and new tobacco products such as electronic nicotine delivery systems (ENDS), heated tobacco products (HTPs) and nicotine patches, and their easy availability and aggressive marketing online Polanska and Kalet, 2021).…”
mentioning
confidence: 99%